Growth and cooperation of Latin American Countries: The role of industrial knowledge - Baquero Cruz, Gesny Yadira; Florez Torres, Greys M.; Hanappi, Gerhard (TECCIENCIA, 2022)
A direct comparison of the welfare implications of pure competition between the states of Latin America and the outcome of a cooperative set of actions of these states is not possible. Laboratory experiments in the social sciences are impossible; societies experience just one run through history. Nevertheless, a concise study of the performance of a specific tool of cooperation, namely the Industrial Knowledge Bank (IKB), can be performed. If over time, such a tool attracts more and more countries, which formerly relied on competitive forces only, then an indirect proof of the superiority of cooperation can be assumed. The industrial knowledge is exchanged via specified projects, which form a network in the IKB data-bank. Then, the evolution of the structure of this network mimics the growth of the actual cooperative industrial projects. This paper provides a brief history and description of this institutional attempt to increase cooperation. It also shows the most relevant bottlenecks met by this project. Further, a clear picture of the state of industrial cooperation across South America is studied in detail through the development of the nodes of this network. We then use two indices typical for welfare increase to compare Latin American countries being part of the cooperation with those not taking part. The visible correlation can be interpreted as a hint of the advantages of cooperation. In conclusion, we provide some possible future scenarios for further industrial development in Latin America based on the study of this Industrial Knowledge Bank.